Jenis-Jenis Penilaian Bahasa Indonesia Di Smp Negeri 1 Surakarta Kurikulum 2013 - Hapsari, Mega Nuri; , Dra. Main Sufanti, M.Hum (2017)
This research aims to describe kinds of assessment implemented in the Indonesian language subject in SMPN 1 Surakarta, to explain the obstacles faced when implementing the assessment. Data from this research is in the form of the taechers' statements about the kinds of assessment, obstacles in implementing the assessment and efforts in coping with the obstacles obtained from terview,uestionnaire and assessment documents which had been implemented. The data sources in this research are five teachers of Indonesian in SMPN 1 Surakarta. Kind of this research is qualitative descriptive. Objects of this research are kinda of assessment, obstacles faced and efforts in coping with the obstacle of assessment implementation. Technique of data collection was conducted through interview, questionnaire and document. Technique of data analysis data in this research used the techniques of content analysis. The results of the research are as follows: (1) There ate eleven assessments conducted: observation, self assessment, peer assessment, journal assessment, written test assessment, oral test assessment, tasking assessment, project asessment, product assessment, performance assessment, and portofolio assessment. (2) Obstacles faced by the teachers when implementing the kinds of assessment cover the obstacle of time limitation, the obatacles of students, subjectivity in the assessment and the obstacles in determining the model in implementing the assessment. (3) Efforts made by the teachers when coping with the obstacles in the assessment implementation are: reestimating the time in implementing the learning, giving motivation to the students, giving time to thw students if any of them had not finished the task yet, and reading several book references on the model of assessment implementation.